The Effect of a Combinatorial Program of Balance - Plyometric Training on Jumping Ability of Taekwondo Athletes - Chasialis Αθανάσιος; Grivas Γεράσιμος; Katsoula Χριστίνα; Varra Βασιλική; Koutsioras Ιωάννης; Drossos Σταύρος (Inquiries in Physical Education and Sport, 2015)
The purpose of this study was to compare the effectiveness of a combined plyometric and balance training program and a simple plyometric training program on jumping ability and balance in adult men athletes of Taekwondo. The sample consisted of twenty (20) adult male Taekwondo athletes aged 18-24 years who were divided into two groups of 10 people. The first group makes plyometric training (PO) while the second group makes, first balance training and then plyometric training (PO+I). The interventionist program to PO+I was twelve weeks and included variants balance training exercises for both feet with or without use of the plank and balance disk and then plyometric training exercises such hoples, jump, triple jump, bounce over obstacles and jumping run. The PO group for the same period made, only plyometric training. Horizontal (standing long jump test) and vertical jumping ability (counter movement jump test), and static (stork test) and dynamic (Bass test) balance were measured prior and 2-days after the completion of training programs. For the statistical analysis of the results, was used analysis of variance with two factors (two-way ANOVA), «group» x «time» (2x2), with repeated measures in factor "time". In addition to for investigating the differences between groups, used the formula of Tukey as the criterion post-hoc comparison, where necessary. From the analysis of the results revealed that only the PO+I group improved static and dynamic balance, while both groups improved significantly the horizontal and the vertical jumping ability without, be differences between them.